FROM THE HISTORY OF ESTABLISHMENT KOREAN COLLECTIVE FARMERS IN FERGHANA VALLEY (American Journal of Interdisciplinary Research and Development, 2023)
This article describes the forced resettlement of the Korean people from the Far East to Central Asia, especially to the areas of Ferghana Valley in the late 30s of the 19th century and the creation of Korean kolkhoz in Andizhan, Namangan and Ferghana.